Escalas do tempo - Landowski, Eric (Revista Acta Semiotica, 2021)
Viral epidemics are processes in which temporality obviously constitutes an essential variable. But different time scales must be distinguished. To see the current pandemic as a singular event is but an illusion due to the “mesoscopic” timescale we are embracing. There is a microscopic scale — that of physiological processes —, a mesoscopic scale, which only allows to see the closest evidence, and a macroscopic scale, that of the ecological determinisms which explain the emergence of the disease in the history of the relationships between species. The article focuses on the mesoscopic level and highlights some semiotic specificities of today’s experience : a temporal suspension, the threat of pure, dramatic and final discontinuity, the behavior of a virus that appears to have “intentionality”, a strong intensity coupled with a long duration, a time of exception, drawn to a final end, and a victory which will only be achieved with great effort.